Antimicrobial resistance of Escherichia coli isolated from freshwaters and hospital effluents in Belgium. (1st March 2022) - Crettels, L.; Burlion, N.; Breyer, R.; Mainil, J.; Servais, P.; Korfer, J.; Thiry, D.
Abstract: The purpose of this work was to evaluate the level of antimicrobial resistant Escherichia coli isolates in freshwaters and hospital effluents in Belgium. The samples were collected from 24 locations along the Ourthe, Vesdre, Amblève and Meuse rivers and in the wastewater effluents of several hospitals. The sampling stations in rivers were classified according to the dominant land covers of the rivers (rural, urban and forest areas). Two sampling campaigns were organized in May and October 2019 to highlight a possible seasonal effect. A total of 938 E. coli strains were isolated on Chromogenic Selective Tryptone Bile X‐glucuronide (TBX) and TBX supplemented with amoxicillin (TBX+AMX) media. Disk diffusion assays were performed following the EUCAST's recommendations to assess the antimicrobial resistance against 12 antibiotics. A total of 32·7% of strains were at least resistant to one antibiotic and 24·6% were multiple antimicrobial resistant strains on TBX. The highest resistance rates were found for ampicillin (AMP), amoxicillin coupled with clavulanic acid (AMC) and sulfamethoxazole/trimethoprim (SXT). The lowest resistance rates were observed for meropenem (MEM) and ertapenem (ETP), which are last resort antibiotics. No significant difference was observed between both campaigns for the resistance rate to antibiotics.